Bacteriostatic and deodorant socks based on coffee carbon modified fibers and preparation method thereof

By using a three-layer composite structure and a low-carbon manufacturing process, the antibacterial properties and washability of antibacterial socks have been improved. This solves the problems of single material function, crude structural design and lack of environmental protection in existing technologies, and achieves highly efficient antibacterial and long-lasting deodorization effects.

CN120982813APending Publication Date: 2025-11-21JINHUA DAHUA KNITTING CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510947966.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-10
Publication Date
2025-11-21

AI Technical Summary

Technical Problem

Existing antibacterial sock materials have limited functionality, crude structural design, lack of environmental friendliness, and poor durability, failing to effectively improve antibacterial performance and washability, and also have low utilization rates of coffee grounds.

Method used

The socks feature a three-layer composite structure: the inner layer is a blend of chitosan-modified coffee charcoal fiber and cotton fiber; the middle layer is polyester yarn covered with nano-germanium particles; and the outer layer is a blend of coffee charcoal fiber and spandex. The heel and toe areas are made with a dense plain knit weave, and the sole has a moisture-wicking groove structure. The socks are made with a low-carbon manufacturing process and an antibacterial synergist.

Benefits of technology

It achieves highly efficient antibacterial performance with an antibacterial rate of over 99.8%, maintains 95% washability after more than 50 washes, improves deodorization performance by 7 times, and optimizes comfort and environmental friendliness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120982813A_ABST
    Figure CN120982813A_ABST
Patent Text Reader

Abstract

The invention provides a bacteriostatic and deodorant sock based on coffee carbon modified fibers and a preparation method of the bacteriostatic and deodorant sock, and belongs to the field of functional textiles. Aiming at the problems of single function, insufficient partition design, poor durability and the like of the existing antibacterial socks, a three-layer composite structure is adopted: the inner layer is made of chitosan modified coffee carbon and cotton blended yarns, the middle layer is made of nano germanium polyester wrap yarns, and the outer layer is made of coffee carbon / spandex rib stitches. The sock heels and the sock toes adopt densified plain stitches and are embedded with the elastic fibers, so that the antibacterial fitness is improved; the sock bottom is provided with a moisture guiding groove and loaded with silver-loaded activated carbon microcapsules, so that sweat guiding is accelerated; regenerated PET is blended with coffee grounds to prepare fibers, and the fibers are subjected to plasma treatment and compound antibacterial agent finishing. The antibacterial rate of the product is greater than 99.8%, the antibacterial rate is still greater than 95% after 50 times of washing, the ammonia adsorption capacity reaches 4.2 mg / g, and the product has high environmental protection property and comfort.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of functional textile products technology, specifically to a zoned antibacterial and deodorizing sock based on coffee charcoal modified fiber and its preparation method, which is particularly suitable for sports socks, health socks and other scenarios requiring long-lasting antibacterial effects. Background Technology

[0002] As a key carrier for regulating the foot's microenvironment, the antibacterial and deodorizing properties of socks directly affect wearing comfort and health. Traditional technologies mainly have the following shortcomings:

[0003] Limited material functionality: Conventional antibacterial socks often use metallic antibacterial agents such as silver ions and copper ions. For example, although CN211558831U has a silver ion layer at the toe, metal ions are easily oxidized and deactivated, and the antibacterial rate decreases by more than 40% after multiple washes. Although bamboo charcoal fiber has adsorption properties, its specific surface area is limited (usually <500m²). 2 / g), cannot provide long-lasting antibacterial protection.

[0004] The structural design is crude: Although existing technologies such as CN201894189U use coffee yarn outer yarn and alloy germanium lining yarn composite, they do not make zoned designs for the different sweat distribution in different areas of the foot, resulting in insufficient antibacterial properties in high-humidity areas (such as between the toes and heels); the toe of the sock is difficult to clean and bacteria remain seriously.

[0005] Environmental shortcomings: Coffee grounds have a low utilization rate as a renewable resource. Conventional coffee charcoal fiber production requires the consumption of new polyester raw materials. For example, CN113930963B directly mixes coffee grounds into polyester melt, resulting in a fiber strength decrease of >30%.

[0006] Poor functional durability: Patent CN221711227U uses an activated carbon sponge pad, but the activated carbon particles are easy to fall off, and the deodorization rate decreases by more than 50% after 10 washes. Summary of the Invention

[0007] The core problems solved by this invention are: how to improve the broad-spectrum antibacterial properties and washability of coffee charcoal fiber; how to achieve sufficient regional antibacterial and moisture-wicking requirements; and how to reduce production costs through the high-value utilization of waste coffee grounds.

[0009] To achieve the above objectives, one aspect of the present invention provides the following technical solution: an antibacterial and deodorizing sock based on coffee charcoal modified fiber, wherein the sock adopts a three-layer composite structure, comprising:

[0010] Inner layer: made of chitosan-modified coffee charcoal fiber and cotton fiber blend, of which chitosan-modified coffee charcoal fiber accounts for 50-70% of the total weight of the inner layer fiber;

[0011] Middle layer: Polyester-covered yarn with embedded germanium nanoparticles, the germanium nanoparticles accounting for 1-3% of the weight of the middle layer fiber;

[0012] Outer layer: Ribbed weave of coffee charcoal fiber and spandex, with spandex accounting for 10-15%;

[0013] The heel and toe areas of the socks are made of high-density plain knit fabric, with a density 20-30% higher than that of the body area, and elastic fibers are embedded in the high-density areas.

[0014] Furthermore, the preparation method of the chitosan-modified coffee carbon fiber includes the following steps:

[0015] (a) Calcine the recycled coffee grounds at 1000-1200℃ in an inert atmosphere for 6-10 hours and grind them into 300-500nm powder;

[0016] (b) Calcined coffee grounds powder and recycled polyester particles are melt-blended at a mass ratio of 1:3-5 and extruded to obtain coffee char masterbatch;

[0017] (c) The coffee charcoal masterbatch is reacted with the chitosan modified solution at 110-130°C for 2-4 hours. The chitosan modified solution contains 5% by mass of chitosan acetic acid solution, 1% nano zinc oxide dispersion and 0.5% epoxy crosslinking agent.

[0018] Furthermore, the bottom of the sock is provided with a moisture-wicking groove structure, which consists of alternating plain knit weave and raised rib strips. The width of the rib strips is 2-3 mm and the spacing is 5-8 mm. Silver-loaded activated carbon microcapsules are attached to the grooves. The microcapsule particle size is 10-20 μm and the amount of attachment is 3-5% of the fiber weight of the sock bottom area.

[0019] Furthermore, the inner blended fiber also includes bamboo charcoal fiber, with a mass ratio of coffee charcoal fiber: cotton fiber: bamboo charcoal fiber of (4-5):(3-4):(1-2), and the specific surface area of ​​the bamboo charcoal fiber is 800-1000 m². 2 / g.

[0020] Secondly, the present invention also provides a method for preparing antibacterial and deodorizing socks based on coffee charcoal modified fibers, comprising the following steps:

[0021] S1. Preparation of chitosan-modified coffee charcoal fiber: Calcinated coffee grounds powder is melt-blended and granulated with recycled PET, then impregnated with chitosan-modified liquid and spun to obtain coffee charcoal fiber with a fineness of 1.2-1.5D; S2. Segmented weaving:

[0022] The hosiery is made using a computerized jacquard knitting machine. The cuffs and legs of the hosiery are made with a dense rib knit structure, with a loop density of 120-130 stitches per inch.

[0023] The back of the sock is made of ribbed fabric with curved stripes, with a stripe spacing of 3-5mm;

[0024] The heel and toe of the socks are woven with a dense plain knit structure using the fibers obtained in step S1 and spandex-covered yarn, with polyester elastic fibers embedded in the dense area;

[0025] S3. Finishing: Immerse the knitted sock blank in a finishing solution containing 2-5% moisture-wicking agent and 1-3% antibacterial synergist at a liquor ratio of 1:15 and treat at 50-60℃ for 20-30 minutes.

[0026] S4. Shaping: Shaping for 15-20 seconds on a steam styling machine at 120-130℃, with overfeed rate controlled at 15-20%.

[0027] Furthermore, the antibacterial synergist is a compound of modified arginine hydrochloride, nano zinc oxide and tea polyphenols in a mass ratio of 3:1:2, and the total concentration in the finishing solution is 1.5-2.5 g / L.

[0028] Furthermore, a plasma treatment is added before finishing in step S3. The treatment conditions are: argon atmosphere, power 300-500W, treatment time 2-5 minutes, so that the etching depth on the fiber surface reaches 0.5-1μm.

[0029] Furthermore, the moisture-wicking groove structure of the sock bottom is prepared using a local hot-pressing molding technology, with a hot-pressing temperature of 180-190℃, a pressure of 0.5-0.8MPa, and a time of 10-15 seconds. Immediately after molding, a suspension of silver-loaded activated carbon microcapsules is sprayed on the material.

[0030] Furthermore, the inner layer of chitosan-modified coffee charcoal fiber has a microporous structure with an average pore size of 50-100 nm and a specific surface area ≥350 m². 2 / g, far-infrared emissivity ≥0.88.

[0031] Furthermore, a support band is provided at the arch of the sock body. This support band is made of double rib knitted outer layer coffee charcoal fiber and middle layer nano-germanium coated yarn, with a width of 15-20mm and a tensile recovery rate of ≥95%.

[0032] The innovation of this invention lies in:

[0033] 1. Synergistic antibacterial effect of three-layer composite fiber structure

[0034] Inner layer: 50-70% chitosan-modified coffee charcoal fiber and cotton fiber blend. The modification method involves melting and granulating coffee grounds into powder by calcination at 1000-1200℃ with recycled PET particles, followed by modification with a chitosan solution containing nano-ZnO. This process creates a microporous-antibacterial molecular composite structure on the fiber surface, with a pore size of 50-100 nm and a specific surface area ≥350 m². 2 / g. This design improves the antibacterial rate by 40% compared to traditional coffee charcoal fiber (CN201894189U), and chitosan and coffee charcoal polyphenols synergistically inhibit bacterial metabolic enzymes.

[0035] Middle layer: Nano-germanium and polyester-coated yarn. 1-3wt% germanium particles are embedded in polyester fibers after surface activation, releasing far-infrared rays with a normal emissivity ≥0.88, which promotes blood circulation and inhibits the growth of anaerobic bacteria.

[0036] Outer layer: coffee charcoal and spandex ribbed fabric. Spandex enhances fit, while coffee charcoal absorbs external odors.

[0037] 2. Structural Design of the Zone:

[0038] The heel and toe areas feature a high-density plain knit weave with embedded polyester elastic fibers. This denser structure increases contact points with the foot, enhancing the massage sensation; the elastic fibers have a recovery rate of >95%, preventing friction-induced odor caused by localized loosening.

[0039] Moisture-wicking grooves on the sole: Composed of alternating 2-3mm wide ribbed strips and plain knit fabric, with silver-loaded activated carbon microcapsules loaded within the grooves. This structure accelerates the directional wicking of sweat, increasing the moisture-wicking rate by 50%, while the microcapsules' slow-release silver ions enhance instantaneous antibacterial effects.

[0040] Arch support band: Double ribbed interwoven band, 15-20mm wide, with a tensile recovery rate of ≥95%, reducing stuffiness caused by foot sliding friction during exercise.

[0041] 3. Low-carbon preparation process

[0042] Coffee grounds recycling: Recycled PET bottles are used to replace virgin polyester. During melt blending, 0.5-1% epoxy chain extender is added to compensate for the loss of molecular weight of recycled materials, so that the fiber strength reaches 4.2 cN / dtex.

[0043] Plasma pretreatment: The fiber surface is etched under an argon atmosphere to achieve a micropore depth of 0.5-1μm, thereby increasing the amount of finishing agent adhering by >30%.

[0044] The antibacterial synergist compound consists of modified arginine hydrochloride which disrupts bacterial cell membranes, nano-ZnO photocatalytic sterilization, and tea polyphenols which provide antioxidant protection. These three factors work synergistically to achieve an antibacterial durability of >90% after 50 washes.

[0045] Beneficial effects of this invention:

[0046] Improved antibacterial performance: Antibacterial rate against Staphylococcus aureus and Candida albicans >99.8%, and still >95% after 50 washes, far exceeding the national standard AA grade requirements;

[0047] Long-lasting deodorization: Ammonia adsorption capacity reaches 4.2mg / g, which is 7 times that of pure cotton socks;

[0048] Comfort optimization: Moisture-wicking grooves increase the rate of moisture evaporation from the soles of the feet by 60%;

[0049] Environmental benefits: 100% utilization rate of coffee grounds, and >40% recycled PET. Attached Figure Description

[0050] Figure 1 This is a schematic diagram of the three-layer structure of the present invention;

[0051] Figure 2 This is a schematic diagram of the process flow of the present invention;

[0052] Figure 3 This is a schematic diagram of the preparation process of chitosan-modified coffee carbon fiber according to the present invention;

[0053] In the diagram, 101 is the outer layer; 102 is the middle layer; and 103 is the inner layer. Detailed Implementation

[0054] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0055] Example 1, as Figure 3 As shown, chitosan-modified coffee carbon fiber preparation

[0056] The recycled coffee grounds were washed, dried, calcined at 1150℃ for 8 hours under nitrogen protection, and then ball-milled to 350nm powder.

[0057] Waste PET bottle fragments are melted, 0.8% epoxy chain extender ADR-4468 is added, and the mixture is extruded and granulated to obtain recycled granules;

[0058] 1.4D coffee charcoal fiber was obtained by melt blending coffee grounds and recycled granules at a mass ratio of 1:4 and spinning.

[0059] The fiber was immersed in a modification solution (5% chitosan acetic acid solution, 1% nano ZnO and 0.5% glutaraldehyde), reacted at 120°C for 3 hours, washed with water and dried.

[0060] Example 2, as Figure 1 , Figure 2 As shown, antibacterial and deodorizing socks are knitted as follows:

[0061] Yarn configuration:

[0062] Inner layer: 60% modified coffee charcoal fiber, 25% combed cotton, and 15% 900m² specific surface area fiber. 2 / g bamboo charcoal fiber, 40S yarn;

[0063] Middle layer: Nano-germanium, polyester, with germanium accounting for 2%, 75D / 48F;

[0064] Outer layer: coffee charcoal fiber and spandex in a ratio of 85:15, 32S.

[0065] Weaving technique:

[0066] Cuffs and legs: 128 stitches / inch high-density rib knit;

[0067] Heel and toe: Enriched plain knit weave, density increased by 25%, with embedded 20D polyester elastic yarn;

[0068] Sole: The sole is formed by hot pressing and moisture-wicking grooves, with rib strips 2.5mm wide and 6mm apart, and sprayed with 10% silver-loaded activated carbon microcapsule liquid with a particle size of 15μm;

[0069] Arch support: 18mm wide double ribbed interwoven support strap.

[0070] Example 3: Post-finishing process

[0071] Plasma treatment: Argon flow rate 15L / min, power 450W, time 4min;

[0072] Impregnation finishing solution: bath ratio 1:15, containing 2% moisture-wicking agent polyether modified siloxane and 1.5% antibacterial synergist mixed with arginine hydrochloride: nano ZnO: tea polyphenols = 3:1:2, treated at 55℃ for 25 min;

[0073] Steam setting: Set at 125℃ for 18 seconds, with an overfeed rate of 18%.

[0074] The performance of the socks prepared by this invention is tested as follows: antibacterial rate: Staphylococcus aureus > 99.9% (98.2% after 50 washes); deodorization: ammonia adsorption capacity 4.3 mg / g; moisture wicking: water evaporation time 8.2 min; durability: after 50 washes, the groove structure is not broken, and the microcapsule residue rate is > 85%.

[0075] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. An antibacterial and deodorizing sock based on coffee charcoal modified fiber, characterized in that: The socks have a three-layer composite structure, including: Inner layer: made of chitosan-modified coffee charcoal fiber and cotton fiber blend, of which chitosan-modified coffee charcoal fiber accounts for 50-70% of the total weight of the inner layer fiber; Middle layer: Polyester-covered yarn with embedded germanium nanoparticles, the germanium nanoparticles accounting for 1-3% of the weight of the middle layer fiber; Outer layer: Ribbed weave of coffee charcoal fiber and spandex, with spandex accounting for 10-15%; The heel and toe areas of the socks are made of high-density plain knit fabric, with a density 20-30% higher than that of the body area, and elastic fibers are embedded in the high-density areas.

2. The antibacterial and deodorizing socks based on coffee charcoal modified fibers according to claim 1, characterized in that: The preparation method of the chitosan-modified coffee carbon fiber includes the following steps: (a) Calcine the recycled coffee grounds at 1000-1200℃ in an inert atmosphere for 6-10 hours and grind them into 300-500nm powder; (b) Calcined coffee grounds powder and recycled polyester particles are melt-blended at a mass ratio of 1:3-5 and extruded to obtain coffee char masterbatch; (c) The coffee charcoal masterbatch is reacted with the chitosan modified solution at 110-130°C for 2-4 hours. The chitosan modified solution contains 5% by mass of chitosan acetic acid solution, 1% nano zinc oxide dispersion and 0.5% epoxy crosslinking agent.

3. The antibacterial and deodorizing socks based on coffee charcoal modified fibers according to claim 1, characterized in that: The bottom of the socks is provided with a moisture-wicking groove structure, which consists of alternating plain knit weave and raised rib strips. The rib strips are 2-3 mm wide and 5-8 mm apart. Silver-loaded activated carbon microcapsules are attached to the grooves. The microcapsule particle size is 10-20 μm and the amount of attachment is 3-5% of the fiber weight of the sock bottom area.

4. The antibacterial and deodorizing socks based on coffee charcoal modified fibers according to claim 1, characterized in that: The inner blended fiber also includes bamboo charcoal fiber, with a mass ratio of coffee charcoal fiber: cotton fiber: bamboo charcoal fiber of (4-5):(3-4):(1-2), and the specific surface area of ​​the bamboo charcoal fiber is 800-1000 m². 2 / g.

5. A method for preparing antibacterial and deodorizing socks based on coffee charcoal modified fibers as described in any one of claims 1-4, characterized in that, Includes the following steps: S1. Preparation of chitosan-modified coffee charcoal fiber: calcined coffee grounds powder is melt-blended and granulated with recycled PET, then impregnated with chitosan-modified liquid and spun to obtain coffee charcoal fiber with a fineness of 1.2-1.5D. S2. Sectional weaving: The hosiery is made using a computerized jacquard knitting machine. The cuffs and legs of the hosiery are made with a dense rib knit structure, with a loop density of 120-130 stitches per inch. The back of the sock is made of ribbed fabric with curved stripes, with a stripe spacing of 3-5mm; The heel and toe of the socks are woven with a dense plain knit structure using the fibers obtained in step S1 and spandex-covered yarn, with polyester elastic fibers embedded in the dense area; S3. Finishing: Immerse the knitted sock blank in a finishing solution containing 2-5% moisture-wicking agent and 1-3% antibacterial synergist at a liquor ratio of 1:15 and treat at 50-60℃ for 20-30 minutes. S4. Shaping: Shaping for 15-20 seconds on a steam styling machine at 120-130℃, with overfeed rate controlled at 15-20%.

6. The method for preparing antibacterial and deodorizing socks based on coffee charcoal modified fibers according to claim 5, characterized in that: The antibacterial synergist is a compound of modified arginine hydrochloride, nano zinc oxide and tea polyphenols in a mass ratio of 3:1:2, and the total concentration in the finishing solution is 1.5-2.5 g / L.

7. The method for preparing antibacterial and deodorizing socks based on coffee charcoal modified fibers according to claim 5, characterized in that: Before finishing in step S3, plasma treatment is added. The treatment conditions are: argon atmosphere, power 300-500W, treatment time 2-5 minutes, so that the etching depth on the fiber surface reaches 0.5-1μm.

8. The method for preparing antibacterial and deodorizing socks based on coffee charcoal modified fibers according to claim 5, characterized in that: The moisture-wicking groove structure of the sock bottom is prepared by local hot pressing molding technology, with a hot pressing temperature of 180-190℃, a pressure of 0.5-0.8MPa, and a time of 10-15 seconds. After molding, a silver-loaded activated carbon microcapsule suspension is sprayed immediately.

9. The antibacterial and deodorizing socks according to claim 1, characterized in that: The inner layer of chitosan-modified coffee charcoal fiber has a microporous structure with an average pore size of 50-100 nm and a specific surface area ≥350 m². 2 / g, far-infrared emissivity ≥0.

88.

10. The antibacterial and deodorizing socks according to claim 1, characterized in that: The sock body has a support band at the arch, which is made of double rib knitted outer layer coffee charcoal fiber and middle layer nano germanium-coated yarn, with a width of 15-20mm and a tensile recovery rate of ≥95%.

Citation Information

Patent Citations

  • Preparation method of warm silk fabric finished with nano coffee carbon material

    CN113930963B

  • Coffee-yarn antibacterium environment-friendly socks

    CN201894189U

  • Antibacterial and deodorant sock

    CN211558831U